The effect of acute Taurine ingestion on endurance performance and metabolism in well-trained cyclists - Rutherford, J. A.; Spriet, L. L.; Stellingwerff, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
This study examined whether acute taurine (T) ingestion before prolonged cycling would improve time-trial (TT) performance and alter whole-body fuel utilization compared with a control (CON) trial and a placebo (PL) trial in which participants were told they received taurine but did not. Eleven endurance-trained male cyclists (27.2 ± 1.5 yr, 74.3 ± 2.3 kg, 59.9 ± 2.3 ml · kg-1 · min-1; M ± SEM) completed 3 trials in a randomized, crossover, blinded design in which they consumed a noncaloric sweetened beverage with either 1.66 g of T or nothing added (CON, PL) 1 hr before exercise. Participants then cycled at 66.5% ± 1.9% VO2max for 90 min followed immediately by a TT (doing 5 kJ of work/kg body mass as fast as possible). Data on fluid administration, expired gas, heart rate, and ratings of perceived exertion were collected at 15-min intervals during the 90-min cycling ride, but there were no differences recorded between trials. There was no difference in TT performance between any of the 3 trials (1,500 ± 87 s). Average carbohydrate (T 2.73 ± 0.21, CON 2.88 ± 0.19, PL 2.89 ± 0.20 g/min) and fat (T 0.45 ± 0.05, CON 0.39 ± 0.04, PL 0.39 ± 0.05 g/min) oxidation rates were unaffected by T supplementation. T ingestion resulted in a 16% increase (5 g, ~84 kJ; p < .05) in total fat oxidation over the 90-min exercise period compared with CON and PL. The acute ingestion of 1.66 g of T before exercise did not enhance TT performance but did result in a small but significant increase in fat oxidation during submaximal cycling in endurance-trained cyclists.